In-vitro anthelmintic potential of strongylodon macrobotrys (Tayabak) and dillenia philippinensis (Katmon) methanol leaf extract against caenorhabditis elegans - Jotham B. Naval Matthew Mark A. Martinez Janiz Alyna A. Ramos Frances Anne DR. Salazar Kim Colline Enriquez 4 0 16; 5
u
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2